Spatial and temporal dynamics of the abundance of crustose calcareous algae on the southernmost coral reefs of the western Atlantic (Abrolhos Bank, Brazil) - Amado-Filho, Gilberto Menezes (2018)
Crustose calcareous algae (CCA) constitute one of the main reef builders on the Abrolhos Bank, Brazil. Once CCA taxonomy is locally understood, differences in growth-forms may be useful for the delimitation of taxa using characteristics such as the presence or absence of surface protuberances. Here, growth-forms were used to identify and quantify the most common CCA taxa on the shallow reefs (3-10 m) of the Abrolhos Bank to determine possible changes in the CCA community over a period of 10 years, and the ecological significance of CCA to local reefs was interpreted. The CCA assemblages were surveyed from 2006-2015 by using fixed photoquadrats at four sites in the inner (10-20 km from the mainland) and mid-shelf reefs (40-75 km from the mainland). The five most common CCA taxa were Pneophyllum conicum, the Lithophyllum kaiserii / Lithophyllum sp. complex, Melyvonnea erubescens, the Hydrolithon boergesenii / Porolithon onkodes complex and Peyssonelia sp. The overall mean CCA cover on the reefs was 20%. A comparison with a previous monitoring study in the same region indicated that the CCA cover nearly doubled from 2003-2008 to 2006-2015. This study reveals that the coral-killing species P. conicum dominated CCA flora on the shallow Abrolhos reefs in the last decade, and the local specific abundance of CCA slightly fluctuated over time and was species-and site-specific. The information obtained in this study contributes to the understanding of the ecology of the key calcifying components of the Abrolhos reefs and provides a useful baseline for exploring the responses of CCA to future environmental changes.